«Չար մշակների» առակի մեկնությունը հայ միջնադարյան քարոզխոսական գրականության մեջ - Բեյլերյան, Հովհաննես («Նաիրի» հրատ.)
Некоторые библейские притчи евангелисты излагают, по-разному акцентируя те или иные эпизоды. Первичной целью толкователей было не только проведение параллелей между этими отрывками, но и раскрытие общего и главного послания Евангелия, которое возможно понять, только если удастся выявить все семантические и контекстуальные слои конкретного слова или эпизода. Отцы Церкви, а позже и толкователи, не только передавали основы истинной доктринальной проповеди, но также старались извлечь из Библии все соответствующие стихи, касающиеся данного эпизода. Особенно в случае интерпретации новозаветной притчи, эти символические структуры ярко выражены и традиционно стабильны. There are examples of apostles retelling well-known biblical parables, variously highlighting the episodes. The initial purpose of the commentators was not only to draw parallels between these passages, but also to reveal the main message of the Gospel, which may be comprehensible only in case of identifying all the semantic and contextual layers of a given word or episode. Church fathers, and later on also commentators, enriched the legacy of previous authors not only by passing on the fundamentals of a true doctrinal preaching, but also by collecting from the Scriptures all the verses relevant to a given episode. Particularly, in case of the interpretation of the New Testament parables, these symbolic structures are vividly expressed and traditionally immutable.
Keywords: Ավետարան; Մեկնաբանություն; Առակ